Pengembangan Media Chemo-Edutainmentmelalui Software Macromedia Flash MX pada Pembelajaran IPA Kimia SMP - Munir Tanrere; Sumiati Side (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2012)
The aims of this research are: 1) to produce an interactive instructional CD- Chemoedutainment that utilizes macromedia flash software for Chemistry instruction at Junior Secondary School; 2) to examine the reliability and effectiveness of learning by using interactive instructional CD-Chemoedutainment through instruction at school. The products in the first year of research are an interactive instructional CD for main material of acid, base and salt. The conclusions of the study are:1) the instructional CD media can be used well by students; and 2) the instructional CD media is effective for improving student learning outcomes.ABSTRAK Penelitian ini bertujuan untuk: 1) menghasilkan media pembelajaran berupa CD interaktif chemo-edutainmentyang memanfaatkan software macromedia flash dalam pembelajaran Kimia SMP; 2) menguji keterandalan dan efektivitas pembelajaran dengan menggunakan CD interaktif chemoedutainment melalui pembelajaran di sekolah. Hasil penelitian tahun pertama adalah CD pembelajaran interaktif untuk materi pokok asam, basa, dan garam. Kesimpulan hasil penelitian, yaitu: 1) media CD pembelajaran dapat digunakan dengan baik oleh siswa; 2) media CD pembelajaran adalah efektif untuk meningkatkan hasil belajar siswa.